Direct and specific effect of sevoflurane anesthesia on rat Per2 expression in the suprachiasmatic nucleus. - Megumi Anzai; Norio Iijima; Shimpei Higo; Ken Takumi; Izumi Matsuo; Keisuke Mori; Yumiko Ohe; Kana Kadota; Toshio Akimoto; Atsuhiro Sakamoto; Hitoshi Ozawa (PLoS ONE, 2013)
BACKGROUND: Our previous studies revealed that application of the inhalation anesthetic, sevoflurane, reversibly repressed the expression of Per2 in the mouse suprachiasmatic nucleus (SCN). We aimed to examine whether sevoflurane directly affects the SCN. METHODS: We performed in vivo and in vitro experiments to investigate rat Per2 expression under sevoflurane-treatment. The in vivo effects of sevoflurane on rPer2 expression were examined by quantitative in situ hybridization with a radioactively-labeled cRNA probe. Additionally, we examined the effect of sevoflurane anesthesia on rest/activity rhythms in the rat. In the in vitro experiments, we applied sevoflurane to SCN explant cultures from Per2-dLuc transgenic rats, and monitored luciferase bioluminescence, representing Per2 promoter activity. Bioluminescence from two peripheral organs, the kidney cortex and the anterior pituitary gland, were also analyzed. RESULTS: Application of sevoflurane in rats significantly suppressed Per2 expression in the SCN compared with untreated animals. We observed no sevoflurane-induced phase-shift in the rest/activity rhythms. In the in vitro experiments, the intermittent application of sevoflurane repressed the increase of Per2-dLuc luminescence and led to a phase delay in the Per2-dLuc luminescence rhythm. Sevoflurane treatment did not suppress bioluminescence in the kidney cortex or the anterior pituitary gland. CONCLUSION: The suppression of Per2-dLuc luminescence by sevoflurane in in vitro SCN cultures isolated from peripheral inputs and other nuclei suggest a direct action of sevoflurane on the SCN itself. That sevoflurane has no such effect on peripheral organs suggests that this action might be mediated through a neuron-specific cellular mechanism or a regulation of the signal transduction between neurons.